Neuronal calcium signaling in chronic pain - Hertle, Anna M.; Simonetti, Manuela (Cell & tissue research, 2014)
Acute physiological pain, the unpleasant sensory response to a noxious stimulus, is essential for animals and humans to avoid potential injury. Pathological pain that persists after the original insult or injury has subsided, however, not only results in individual suffering but also imposes a significant cost on society. Improving treatments for long-lasting pathological pain requires a comprehensive understanding of the biological mechanisms underlying pain perception and the development of pain chronicity. In this review, we aim to highlight some of the major findings related to the involvement of neuronal calcium signaling in the processes that mediate chronic pain.
Gesehen am 04.09.2020